1998
DOI: 10.1111/j.1469-7793.1998.379bq.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the gating behaviour of human and murine cystic fibrosis transmembrane conductance regulator Cl channels expressed in mammalian cells

Abstract: To investigate the function of the murine cystic fibrosis transmembrane conductance regulator (CFTR), a full‐length cDNA encoding wild‐type murine CFTR was assembled and stably expressed in Chinese hamster ovary (CHO) cells. Like human CFTR, murine CFTR formed Cl− channels that were regulated by cAMP‐dependent phosphorylation and intracellular ATP. However, murine CFTR Cl− channels had a reduced single‐channel conductance and decreased open probability (Po) compared with those of human CFTR. Analysis of the dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 45 publications
6
79
0
Order By: Relevance
“…However, in contrast to the C127 cells, the absolute magnitude of the cAMP-induced ⌬I sc in the NBF1-expressing MGEF monolayers was approximately the same as in the MGEN monolayers expressing recombinant hCFTR. This variance may reflect differences in the activities of the recombinant vs. the endogenous CFTR channel or result from inherent differences in ⌬F508 CFTR properties between the two species (30). Interestingly, the basal I sc of the NBF1-expressing MGEF and MGEN cells was elevated compared with the Zeocinexpressing control monolayers.…”
Section: Discussionmentioning
confidence: 84%
“…However, in contrast to the C127 cells, the absolute magnitude of the cAMP-induced ⌬I sc in the NBF1-expressing MGEF monolayers was approximately the same as in the MGEN monolayers expressing recombinant hCFTR. This variance may reflect differences in the activities of the recombinant vs. the endogenous CFTR channel or result from inherent differences in ⌬F508 CFTR properties between the two species (30). Interestingly, the basal I sc of the NBF1-expressing MGEF and MGEN cells was elevated compared with the Zeocinexpressing control monolayers.…”
Section: Discussionmentioning
confidence: 84%
“…Human and mouse CFTR share only 78% identity at the amino acid level, 35 and there are studies that have identified differences in channel properties between murine and human CFTR. 36 It has also been reported that the interaction of mouse and human CFTR with ENaC is species specific. 37 Thus it is possible that the human CFTR, due to sequence differences, does not function properly in mouse cells under all conditions.…”
Section: Cftr Expression In Murine Ciliated Cells Le Ostrowski Et Almentioning
confidence: 99%
“…The TaqMan EmCFTR RT-PCR assay forward primer (5'-TCGTGATCACATCAGAAATT ATTGATAAT), reverse primer (5'-CCACCTCTCTCAA GTTTTCAATCAT) and fluorogenic probe (5'-CGCTGATTCCCAACAATATGCCTTAACAGAATA) detected endogenous murine CFTR mRNA. The EmCFTR RT-PCR forward primer hybridised to the region of the mCFTR cDNA previously mutated to remove a cryptic bacterial promoter, 6 in order to eliminate hybridisation to mCFTR sequences in the vector pCIKmCFTR.…”
Section: Real-time Quantitative Taqman Rt-pcrmentioning
confidence: 99%
“…The murine CFTR cDNA, isolated from the C57/B6 mouse strain (obtained from B Wainwright and D Lunn, University of Queensland, Brisbane, Australia), was supplied in plasmid pEFmCFTR. 6 The 5' region of the mCFTR cDNA was amplified by PCR from pEFmCFTR using Vent DNA polymerase (New England Biolabs (NEB), Hitchin, UK), and 500 nM forward (GGCTAGCCACCATGCAGAAGTCGCCTTGG) and reverse (CCAGTACTTTATACTCTTGTTTCTGCAGG) primers, and ligated into the plasmid pBluescript SK(Ϫ) (pBSKM) digested with SmaI, to produce pBSKM5' mCFTR. A 290 bp HindIII-SalI fragment of the plasmid pSL301 (Invitrogen, Leek, The Netherlands) multiple cloning site was isolated, and ligated into the low copy number plasmid pBR322 (NEB) digested with HindIII and SalI, to produce pBRSL.…”
Section: Plasmid Expression Vectorsmentioning
confidence: 99%
See 1 more Smart Citation